Pengembangan Pariwisata Berbasis Nilai Budaya, Lingkungan dan Ekonomi Pada Desa Wisata Lerep - Yuniningsih, Tri; Azhar, Aufa Ghifari Fahrezi (Jurnal Ragam Pengabdian, 2026)
Tourism village development is a local potential-based development strategy that promotes community economic growth, cultural preservation, and environmental sustainability. This study aims to analyze tourism development based on cultural, environmental, and economic values in Lerep Tourism Village. The research employed a descriptive qualitative approach using the Community-Based Tourism (CBT) concept. Data were collected through interviews, observations, documentation, and literature review. The findings indicate that tourism development in Lerep Tourism Village is supported by rich local cultural heritage, natural attractions, and active community participation through the Tourism Awareness Group (Pokdarwis) and Village-Owned Enterprise (BUMDes). From the cultural perspective, the village has successfully preserved local traditions while transforming them into educational tourism attractions. Environmentally, tourism development emphasizes sustainable natural resource management and environmental conservation. Economically, the tourism village has created business opportunities, increased local income, and strengthened the village economy. However, several challenges remain, including unequal community participation, suboptimal environmental management, and limited digital promotion. Therefore, stronger collaboration among stakeholders, capacity building for local communities, and innovative tourism management are essential to ensure sustainable and inclusive tourism development.